PENGARUH MEDIA ADOBE FLASH DALAM PEMBELAJARAN FIQIH - Rohman, Miftakhul; Yasin, Muhammad; Marwan, Iwan (Edudeena : Journal of Islamic Religious Education, 2017)
Abstract: Based on preliminary observation note that, in learning activities, teachers deliver materials with power point media less attract students to be active, this is seen only passive students in learning activities. Such activities make students less motivated. The purpose of this study is 1) Describe the implementation of student learning jurisprudence through the application of Adobe Flash media. 2) Describe the learning activities of jurisprudence students through the application of Adobe Flash media. 3) Describing the results of study of jurisprudence of students of Blitar City through the application of Adobe Flash media on basic competence “Explaining the provisions of inheritance law in Islam.” Based on the results of research can be concluded that the application of Adobe Flash media can improve the activity and learning outcomes of students, apply and develop Adobe Flash media in learning jurisprudence with material Explain the provisions of inheritance law in Islam more deepened. Abstrak: Berdasarkan observasi awal diketahui bahwa, pada kegiatan pembelajaran, guru menyampaikan materi dengan media power point kurang menarik siswa untuk aktif, hal ini terlihat siswa hanya pasif dalam kegiatan pembelajaran. Kegiatan yang demikian membuat siswa kurang termotivasi. Tujuan dari penelitian ini adalah 1) Mendeskripsikan pelaksanaan pembelajaran fiqih siswa melalui penerapan media Adobe Flash. 2) Mendeskripsikan aktivitas belajar fiqih siswa melalui penerapan media Adobe Flash. 3) Mendeskripsikan hasil belajar fiqih siswa Kota Blitar melalui penerapan media Adobe Flash pada kompetensi dasar “Menjelaskan ketentuan hukum waris dalam Islam.” Berdasarkan hasil penelian dapat disimpulkan bahwa penerapan media Adobe Flash dapat meningkatkan aktivitas dan hasil belajar fiqih siswa, untuk itu disarankan agar guru menerapkan dan mengembangkan media Adobe Flash dalam pembelajaran fiqih dengan materi Menjelaskan ketentuan hukum waris dalam Islam yang lebih diperdalam.